HIYANGAN WADIAN DALAM UPACARA IJAMBE PADA MASYARAKAT DAYAK MAANYAN - Dwiani Septiana (Balai Bahasa Nusa Tenggara Barat, 2016)
The main problem of this reserach is the study of textual stucture in Hiyangan Wadian at death ceremony in Dayak Maanyan. In order to find and indentify the textual structure that build the Hiyangan Wadian in this ceremony, there are three textual sturcture by Van Dijk, such as macro structure, superstucture, and micro structure. Result of analysis on textual structure in the macro structure found that the main theme in Hiyangan kiaen tell about the journey stages to heaven that have to be passed by the spirit. The super structure of the text reveal that Hiyangan kiaen has three parts, opening part, content part and closing part. Result of analysis in the micro srtucture found that there are lexicosemantic paralelisms that reveal the words repetitions with the same meaning to emphasize that those words are important parts in the text.